Rearrangements of ribosomal DNA clusters in late generation telomerase-deficient Arabidopsis - Siroky, Jiri; Zluvova, Jitka; Riha, Karel; Shippen, Dorothy E; Vyskot, Boris (Chromosoma, 2003)
The ends of eukaryotic chromosomes are capped with special nucleoprotein structures called telomeres. Telomere shortening due to telomerase inactivation may result in fusion of homologous or heterologous chromosomes, leading to their successive breakage during anaphase movement, followed by fusion of broken ends in the next cell cycle, i.e. the breakage-fusion-bridge (BFB) cycle. Using fluorescence in situ hybridization (FISH) with 25S rDNA and specific bacterial artificial chromosome (BAC) probes we demonstrate participation of chromosomes 2 and 4 of Arabidopsis thaliana AtTERT null plants in the formation of anaphase bridges. Both homologous and non-homologous chromosomes formed transient anaphase bridges whose breakage and unequal separation led to genome rearrangement, including non-reciprocal translocations and aneuploidy. The 45S rDNA regions located at the ends of chromosomes 2 and 4 were observed in chromosome bridges at a frequency approximately ten times higher than expected in the case of random fusion events. This outcome could result from a functional association of rDNA repeats at nucleoli. We also describe increased variation in the number of nucleoli in some interphase cells with supernumerary rDNA FISH signals. These data indicate that dysfunctional telomeres in Arabidopsis lead to massive genome instability, which is induced by multiple rounds of the BFB mechanism.
Keywords: genová přestavba; nestabilita genomu; hybridizace in situ fluorescenční; Chromosomes, Plant; buněčné jadérko; DNA, Ribosomal; Anaphase; Gene Rearrangement; In Situ Hybridization, Fluorescence; anafáze; ribozomální DNA; Chromosomes, Artificial, Bacterial; Genomic Instability; telomerasa; chromozomy rostlin; Telomerase; Telomere; telomery; Cell Nucleolus; Arabidopsis; umělé bakteriální chromozomy